2015
DOI: 10.5551/jat.25841
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Plasma PCSK9 Levels and Platelet Indices in Patients with Stable Coronary Artery Disease

Abstract: Aim: Recent studies have shown that platelet indices are linked to metabolic and cardiovascular diseases, in addition to being markers of hemostasis. These studies suggested that they could be modified by various biomolecules, including lipids. Proprotein convertase subtilisin/kexin type 9 (PCSK9), a newly-identified member, plays a key role in lipid metabolism and atherosclerosis. Therefore, we evaluated the relationship between the plasma PCSK9 level and platelet indices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 23 publications
1
36
0
Order By: Relevance
“…In our initial search, 26 studies were found and we limited the analysis to those with subjects aged at least 18 years and acute medical process or intervention without a ‘baseline' plasma draw. This eliminated 11 studies, leaving 15 for analysis [10,11,12,13,14,15,16,17,18,19,20,21,22]. Pooled medians were reported with 95% confidence intervals.…”
Section: Methodsmentioning
confidence: 99%
“…In our initial search, 26 studies were found and we limited the analysis to those with subjects aged at least 18 years and acute medical process or intervention without a ‘baseline' plasma draw. This eliminated 11 studies, leaving 15 for analysis [10,11,12,13,14,15,16,17,18,19,20,21,22]. Pooled medians were reported with 95% confidence intervals.…”
Section: Methodsmentioning
confidence: 99%
“…[5] The association of increased MPV, PDW, P-LCR, and platelet count with diseases related to endothelial dysfunction such as metabolic syndrome, diabetes, coronary artery disease (CAD), and malignancy has been shown in many studies. [6,7,8,9] The newer hematological analyzers are giving variety of platelet parameters which helps in easy detection of change in platelet structure, which may help in early detection of prothrombotic state of the platelets. These can act as an alarm for diagnosing initiation/progression of diabetic complications.…”
Section: Introductionmentioning
confidence: 99%
“…Platelets are a central element of the athero-thrombotic process due to their prothrombotic and proinflamatory function [8,9,10]. The association of increased MPV, PDW and decreased platelet count with disease related to endothelial dysfunction such as metabolic syndrome diabetes, coronary artery disease (CAD) and malignancy which has been shown in many studies [11][12][13][14][15]. Diabetes particularly DMT2 patients are exposed to the increased platelet reactivity due to multi factorial causes such as metabolic (e.g hyperglycemia, hypertriglyceridemia) and systemic abnormalities (eg.…”
Section: Introductionmentioning
confidence: 99%